Language, Power, and Identity: A Sociolinguistic Study of The Alas Language - Hasrul, Saddam; Barus, Efendi; Manugeren (ENGLISH JOURNAL OF INDRAGIRI, 2026)
This study investigates Mekhadat, a ritual speech performed in Alas wedding ceremonies, from a sociolinguistic perspective focusing on language, power, and identity. Using qualitative methods, including participant observation and interviews with community elders, the study explores how Mekhadat embodies ecological metaphors, symbolic authority, and cultural identity. The findings reveal that natural and agricultural imagery, such as rice and water, is central to the discourse, reflecting the Alas community's ecological worldview and their emphasis on fertility, harmony, and prosperity. The study also highlights the power dimension, where only elders or traditional leaders are authorized to deliver Mekhadat, thus legitimizing authority through language in line with Bourdieu's notion of symbolic power. Furthermore, Mekhadat functions as a cultural marker, strengthening collective identity and transmitting values ​​across generations. These findings suggest that Mekhadat is not simply a ritual performance but also a place where ecological wisdom, social hierarchy, and cultural identity converge. This study contributes to broader discussions in sociolinguistics by demonstrating how ritual discourse in minority languages ​​functions as a medium for cultural continuity and symbolic negotiation